Voltage stability assessment for distrbuted generation in islanded microgrid system - Hendi Gareh, Saleh Ali Ahmed (2012)
The increasing energy demands are stressing the generation and transmission capabilities of the power system. Distributed generation (DG), which generally located in distribution systems, has the ability to meet some of the growing energy demands. However, unplanned application of individual distributed generators might cause other technical problems. The microgrid concept has the potential to solve major problems arising from large penetration of DG in distribution systems. A microgrid is not a forceful system when it is compared to a power system. This project proposes a simulation approach to study voltage stability index (VSI) and voltage stability analysis in microgrid system for the improvement of the dynamic voltage stability in a microgrid in case of the dynamic voltage insufficiency. A model of IEEE-14 Bus System has been presented as a case study of an islanded microgird system. This project also presented line voltage stability index analysis which accurately performs voltage stability analysis at each transmission line and precisely predicts voltage collapse on power systems. A formula to calculate VSI has been derived and applied on two cases on the system. To show the effectiveness of the proposed voltage stability analysis method, this approach is implemented in a microgrid test system (14-bus, 20 lines) in PSAT which is a MATLAB toolbox environment. The test system has four diesel DGs and a wind turbine connected with eleven constant loads. The dynamic simulation of the test system is carried out for various types of disturbances. Islanded mode of operation is considered in this study. Fast Voltage Stability Index (FVSI) and voltage stability analysis have been successfully implemented and analysed.